Efeito do desgaste com instrumentos diamantados e da degradação a baixas temperaturas no comportamento mecânico de uma cerâmica Y-TZP - Pereira, Gabriel Kalil Rocha (2014)
Objectives: (1) Compare the effects of grinding on a Y-TZP ceramic executed by diamond discs and diamond burs (with similar grit sizes) in the micromorphology of surface, phase transformation (t®m), flexural strength and structural reliability (Weibull analysis), (2) evaluate the effect of LTD (low-temperature degradation) in the outcomes mentioned above. Methods: Three hundred and sixty discs (15mm x 1,2 mm) of Y-TZP were made according to ISO 6872 2008 for flexural strength determination on ceramic materials and sintered according to the manufacturer`s instructions, than they were divided into groups according to two factors in study: surface treatment - 5 levels (without treatment, extra-fine diamond bur, 600-grit diamond disc, coarse diamond bur and 120-grit diamond disc) and LTD on 2 levels (with and without). For grinding with diamond discs a polishing machine was employed, while for grinding with diamond burs a device was employed to assure the perpendicularity between diamond tip and abrading surface, that way the abrasion movements and the applied pressure were standardized. The LTD was induced in an autoclave at 134ºC under 2 bar for 20 hours. Results: Our findings support that LTD although promoted increase in mphase content and micromorphological alterations did not promoted decrease in zirconia s mechanical properties, grinding at a first moment did not affected too, but when ground Y-TZP was submitted to the LTD effects, the defects introduced by grinding could be detrimental to the material`s resistance. From a methodological point of view, diamond discs should not be employed to simulate clinical abrasion performed with diamond burs on Y-TZP ceramics. Conclusion: Thus grinding of zirconia should be avoided and when it was really necessary tools with low grit sizes should be employed.